Women’s Rebellion against Patriarchal Society as Reflected in Ayu Utami’s Si Parasit Lajang and Pengakuan Eks Parasit Lajang - Anastasia Sidharta (FKIP Universitas Cenderawasih, 2024)
This study examines the influence of patriarchal culture in Indonesia and the active response of feminist literary criticism through the analysis of Ayu Utami's novels